Hemoglobin Agenogi in Argentina: Case Report - Martin, Ana Paula (2012)
Hb Agenogi [b90(F6)Glu–>Lys], a beta chain variant was detected in a 44-years-old female patient of italian ancestry. She showed a hypochromic microcytic anemia and was treated as ferropenic anemia since she was 27 years old. The complete cell blood count revealed the following results: RBC: 4.01× 1012/L, PCV:30.9%, Hb:10.4 g/dl, MCV: 77fl, RDW 13.5%, MCH: 25.9 pg, MCHC:33.7%; reticulocytes: 0.6% and the peripheral blood smear showed no basophilic stippling. Serum vitamin B12, folate, iron, transferrin, transferrin saturation and ferritin were normal. The electrophoresis performed on agarose (alkaline pH) revealed a band of 44.5% with a mobility between Hb C and S. The unstable hemoglobin test was positive and the P50 was 31.3 mmHg (NR: 24 –28 mm Hg). This slow-moving hemoglobin, mild unstable and with decreased oxygen affinity was further characterized by sequencing of the amplified DNA, showing the substitution of glutamic acid (GAG) to lysine (AAG) at position 90 of the β globin chain This mutation has been described in only nine families, this is the second affected case in Argentina.